Estudio del efecto del tamaño de partícula de la dieta sobre la composición química de la carne en cuyes - Lopez Torres, Kevin Patricio (2024)
Meat is the muscle tissue of animals; its chemical composition varies according to some factors such as species, age, type of feeding, environment, and slaughter quality. We aimed the present research work to study the effect of dietary particle size on the chemical composition of guinea pig meat. We used Thirty 15-day-old animals of the A1 line, which we distributed in three experimental groups according to a completely randomized design. We evaluated three diets (treatments) with different particle sizes: T1: fine particle, T2: 50% fine, and 50% coarse particle, and T3: 10 days after the start of the trial, we slaughtered the animals to take muscle samples that were frozen and freeze-dried for the corresponding analysis we determined; moisture, protein, ash; and fat content in the bromatology laboratory of the National University of Loja; we subjected to analysis the data obtained for each variable of variance with the InfoStat program. The results of all variables showed no statistical difference; moisture content averaged 77.85%, crude protein was around 17.01%, ash content reached an average value of 0.85%, and fat was around 5.68%. We concluded that the particle size of the diet does not influence the chemical composition of the guinea pig meat.